Desain Monitoring Sistem pada Tungku Pembakaran dengan Pendekatan Multi-level Digital Twin - Taryana, Galih Purnama; Prasetio, Murman Dwi; Astuti, Murni Dwi; Ayudita Oktafiani; Budiasih, Endang; Wiyono (Jurnal Sistem Cerdas, 2023)
Abstract-Industry 4.0 discusses concepts related to intelligent systems. There are many concepts related to intelligent systems, one of which is the digital twin concept. The digital twin concept as a data acquisition tool is used to build digital information for a physical system. The company is a producer of murando glazed tiles. in the roof tile production process at the company, there are defective rooftiles produced by the company, namely white stone defects and cracked roof tiles. Cracked roof tiles are caused by inappropriate temperatures during the firing process. With a temperature monitoring system in the roof tiles furnace, combustion temperatures can be monitored in real-time. Monitoring system design using a multi-level approach can describe in detail the architecture of the monitoring system based on the digital twin concept. The website is designed using the Human Centered Design method so can produce a website user interface that is in line with the goals and needs of the user. The monitoring system can provide real-time information on the temperature of the roof tiled anywhere with a design that suits the user's needs.